Preparing for War or Peace: Exploring the Peace Values in 9th Grade English Textbook in Khyber Pakhtunkhwa - Kaukab Saba (University of Chitral Journal of Linguistics and Literature, 2023)
Out of many other global issues, one of the most threatening to human beings is war and conflict. Making this world a peaceful abode is the objective of many institutions and Education is one of them. Language teaching can serve as a very effective tool to inculcate peace among the students who build a peaceful nation in return. The study aims to explore the elements of peace values in English textbooks of grade 9th taught in schools of Khyber Pakhtunkhwa. Textbooks are not only used for transferring knowledge of the respective subject but also to bring social reformation to society. The study is qualitative in nature and falls under the constructivist paradigm. The study can be significant for curriculum developers, textbooks writers, teachers, and students to make them aware of the importance of peace development through textbooks. The study followed the theoretical framework of Balasooria (2011) to identify peace values. The findings have shown that social peace value is the most dominant in use in the textbook besides other categories, inner peace, and peace for nature. Moreover, the analysis has revealed that addressing issues like human rights awareness, gender equality, and mental health is lacking in the text which can become a reason for conflict and restlessness in the society eventually leading to a threat to the peace of the society.